RTS,S/AS01 malaria vaccine pilot implementation in western Kenya: a qualitative longitudinal study to understand immunisation barriers and optimise uptake - Jenna Hoyt; George Okello; Teresa Bange; Simon Kariuki; Mohamed F. Jalloh; Jayne Webster; Jenny Hill (BMC, 2023)
Abstract Background Malaria is a significant public health threat in sub-Saharan Africa, particularly among children. The RTS,S/AS01 malaria vaccine reduces the risk and severity of malaria in children. RTS,S/AS01 was piloted in three African countries, Ghana, Kenya and Malawi, to assess safety, feasibility and cost-effectiveness in real-world settings. A qualitative longitudinal study was conducted as part of the feasibility assessment. This analysis explores RTS,S/AS01 vaccination barriers and identifies potential motivators among caregivers in three sub-counties in western Kenya. Methods A cohort of 63 caregivers with a malaria vaccine eligible child was interviewed at three time points over 24 months. A sub-set of 11 caregivers whose eligible children were either partially or non-vaccinated were selected for this sub-analysis. The 5A Taxonomy for root causes of under-vaccination was used to organise the inductively-coded data into categories (awareness, acceptance, access, affordability, and activation) and identify the factors influencing uptake across caregivers. A trajectory analysis was conducted to understand changes in factors over time within each caregiver experience. Caregiver narratives are used to illustrate how the factors influencing uptake were interrelated and changed over time. Results Lack of awareness, previous negative experiences with routine childhood immunisations and the burden of getting to the health facility contributed to caregivers initially delaying uptake of the vaccine. Over time concerns about vaccine side effects diminished and anticipated vaccination benefits strongly motivated caregivers to vaccinate their children. Persistent health system barriers (e.g., healthcare provider strikes, vaccine stockouts, negative provider attitudes) meant some children missed the first-dose eligibility window by aging-out. Conclusions Caregivers in this study believed the RTS,S/AS01 to be effective and were motivated to have their children vaccinated. Despite these positive perceptions of the malaria vaccine, uptake was substantially hindered by persistent health system constraints. Negative provider attitudes emerged as a powerful deterrent to attending immunisation services and hampered uptake of the vaccine. Strategies that focus on improving interpersonal communication skills among healthcare providers are needed.